Manifestation of Clinical Categories of Ocular Graft-versus-Host Disease - Yuan Qiu; Jing Hong; Rongmei Peng (Journal of Ophthalmology)
This study aims at improving the understanding of the subjective symptoms and signs of two different clinical categories of ocular graft-versus-host disease. After reviewing and screening 193 posthematopoietic stem cell transplantation (HSCT) patients of Peking University Third Hospital, we enrolled 148 (21 acute ocular GVHD, 127 chronic ocular GVHD). Patients’ subjective symptoms, ocular parameters, and typical ocular signs were collected and evaluated at the same visit. Classic acute ocular GVHD patients had variable levels of conjunctival involvement but few had keratopathy; increased mucus secretion (21 of 21, 100.0%), red eye (19 of 21, 90.5%), and lacrimation (11 of 21, 52.4%) were the characteristic symptoms. The classic chronic ocular group had severe eye dryness and further corneal lesions, including filamentary keratitis, corneal ulcer, and corneal vascularization. Eye dryness (115 of 127, 90.6%), increased fibrous secretion (53 of 127, 41.7%), photophobia (50 of 127, 39.4%), and alacrimia (45 of 127, 35.4%) were the most common symptoms. Although 44.1% (56 of 127) of these patients had a history of acute ocular GVHD episodes, most were overlooked, so they did not receive stepwise evaluation and treatment. Management of ocular GVHD is very challenging and requires cooperation among disciplines.